2018
DOI: 10.1111/ejn.13871
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive brain stimulation of motor cortex induces embodiment when integrated with virtual reality feedback

Abstract: Previous evidence highlighted the multisensory‐motor origin of embodiment – that is, the experience of having a body and of being in control of it – and the possibility of experimentally manipulating it. For instance, an illusory feeling of embodiment towards a fake hand can be triggered by providing synchronous visuo‐tactile stimulation to the hand of participants and to a fake hand or by asking participants to move their hand and observe a fake hand moving accordingly (rubber hand illusion). Here, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…However, important methodological details can account for this difference. Indeed, the present study was devised to record MEPs at the end of the experimental procedure as a physiological measure of the M1 excitability, as well as a recent study showing that M1 stimulation induces embodiment when integrated with virtual reality feedbacks and obtaining similar negative data on the MEPs amplitude (Bassolino et al., ). On the contrary, the previous study of della Gatta et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, important methodological details can account for this difference. Indeed, the present study was devised to record MEPs at the end of the experimental procedure as a physiological measure of the M1 excitability, as well as a recent study showing that M1 stimulation induces embodiment when integrated with virtual reality feedbacks and obtaining similar negative data on the MEPs amplitude (Bassolino et al., ). On the contrary, the previous study of della Gatta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has emerged showing promising therapeutic applications for the combined use of VR and tES (more specifically tDCS) [ 23 26 ], as well as VR and TMS [ 27 – 29 ], with outcomes not achievable by using either technique individually. Despite the reported promising results, the literature still lacks a systematic review covering the reported methods, outcomes, and potential therapeutic applications in neurological rehabilitation, on the combination of VR and NIBS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the generalizability of the findings is limited by the number and the heterogeneity of the studies included. Bassolino et al (2018) induced embodiment for an artificial hand in a virtual environment through TMS over corticospinal tract, without tactile cues on the hand's skin, typically used to ease rubber hand illusion. Authors argued that this illusory embodiment was determined by neuro-visual integration between TMS over primary motor cortex (and connections with sensory cortex) and hand twitches with visual VR feedback (Bassolino et al, 2018).…”
Section: The Clinical Application Of Nibs and Vrmentioning
confidence: 99%
“…Bassolino et al (2018) induced embodiment for an artificial hand in a virtual environment through TMS over corticospinal tract, without tactile cues on the hand's skin, typically used to ease rubber hand illusion. Authors argued that this illusory embodiment was determined by neuro-visual integration between TMS over primary motor cortex (and connections with sensory cortex) and hand twitches with visual VR feedback (Bassolino et al, 2018). This effect did not occur when sham TMS was delivered, suggesting that the temporal synchrony between active TMS and VR feedback determined the illusory embodiment.…”
Section: The Clinical Application Of Nibs and Vrmentioning
confidence: 99%